The Invasive Plant, Alliaria petiolata, Is an Ecological Trap for the Native Butterfly, Anthocharis midea, in North America - Danielle M. Thiemann; Don Cipollini (Insects)
The introduction of novel plant species to new habitats may have consequences for native herbivores. We examined the impact of Alliaria petiolata, a Eurasian invader of forest understories and edges in North America, on adult oviposition behavior and on larval preference and the performance of Anthocharis midea, a univoltine butterfly that specializes on plants in the Brassicaceae. We compared the usage of A. petiolata by this butterfly to that of one of its common native hosts, Cardamine concatenata, and additionally explored the impact of drought and larval age on the larval success of these hosts. In the field, adults oviposited on the native host preferentially earlier in the season, but they strongly preferred A. petiolata later in the season and laid more eggs overall and in multiples more often on this plant. Larvae strongly preferred to feed on leaves of C. concatenata over A. petiolata in the laboratory and survived to pupation at a high rate on it. Conversely, larvae fed little and died when offered A. petiolata. Larvae preferentially chose tissues of droughted C. concatenata over well-watered plants, but drought stress had no impact on larval mass and survival to pupation. Larvae showed no preference for droughted or non-droughted A. petiolata and while drought stress tended to extend survival on this plant, all larvae still died on it. Older larvae were no better at feeding and surviving on A. petiolata than young larvae. Our results indicate that A. petiolata currently serves as an ecological trap for A. midea, being both highly attractive to ovipositing adults yet lethal to larvae. This effect could cause both local declines in the abundance of this butterfly and drive selection for the altered behavior of adults and larvae to either avoid or better tolerate this plant.